Hukum Islam dan Ketatanegaraan (Sebuah Transformasi Hukum dalam Masyarakat) - Ashadi L Diab (Al-'Adl, 2016)
The paper elaborates transformation of Islamic law in constitution of Indonesia, in which the problem is what the position and Islamic law existence in the system of Indonesia constitution. By seeing various social phenomena and fact that occur in society to do activities and action related to the law. Islamic law in Indonesia is a chain which is not possible to be separated from the historic fact/long history experienced by this nation. Since proclaimed independence of Indonesia on 17 August 1945, it is started the new era of law system in the world of Archipelago which separate between colonial law and system of national law. There are many contradictions and controversy to build national law system, because the laws are not completely based on customary law and Islamic law as well as western law. So the form of constitution is an effort to make a change to something that had already existed, they are adaptation and change. The process or transformation effort of Islamic law to the national constitution was meant as an attempt to apply normative Islamic law to positive Islamic law or usually called positivism Islamic law to the constitution of Indonesia. Constitution perspective has balance to relation among state, law, and religion. Religion is the first component which is in the deepest circle position, proved by the first moral principle of the Pancasila that is there is only one God. Islamic law principles which becomes ideal basic of fiqih they are: Principle of tauhidullah, Principle of insaniyah, Principle tasamuh, Principle of ta’awun, Principles of silaturahim bain annas, Principle of justice, and Principle of benefit.